Dinuclear CoIIYIIIvs. tetranuclear CoII2YIII2 complexes: the effect of increasing molecular size on magnetic anisotropy and relaxation dynamics. Issue 39 (26th September 2019) - Masegosa, Alberto; Palacios, María A.; Ruiz, Eliseo; Gómez-Coca, Silvia; Krzystek, J.; Moreno, José M.; Colacio, Enrique
Abstract : The lower distortion of the Co II ions in the new tetranuclear CoII2YIII2 complex leads to a larger magnetic anisotropy than in its Co II Y III counterparts, whereas its larger size and flexibility seem to promote a faster relaxation dynamic. Abstract : A new CoII2YIII2 complex with the formula [{Co(μ-L)Y(NO3 )}2 (μ-CO3 )2 ]·2CH3 OH·2H2 O (where H2 L = N, N ′, N ′′-trimethyl- N, N ′′-bis(2-hydroxy-3-methoxy-5-methylbenzyl)diethylenetriamine) has been prepared and its structure solved by single-crystal X-ray diffraction. The tetranuclear structure is formed by the connection of two [Co(μ-L)Y(NO3 )] dinuclear units through two carbonate bridging ligands, which exhibit a μ3 -κ 2 -O, O′:κ-O:κ-O′′ tetradentate coordination mode. The Co II ion exhibits a slightly distorted octahedral CoN3 O3 coordination environment. From direct-current magnetic data a large and positive axial anisotropy parameter was extracted ( D = +80.6 cm −1 ) and its sign unambiguously confirmed by HFEPR spectra and ab initio calculations. The extracted D value is rather larger than those previously reported for the analogous Co II Y III dinuclear complexes, which agrees with the fact that the Co II ion in the CoII2YIII2 complex exhibits a lower distortion from the octahedral geometry in this family of CoII n YIII n complexes. Dynamic ac magnetic measurements show that the reported compound presents field-induced slow relaxation for magnetization reversal, through a combination of direct and Raman processes. Magnetic measurements on the diluted magnetic counterpart (Zn/Co = 10/1) show the persistence of these processes, pointing out their single-ion origin. The Raman relaxation process for the CoII2YIII2 complex is faster that those observed for its Co II Y III dinuclear counterparts. This fact and the existence of the persistent direct process at low temperature could be attributed to the former molecule being larger and more flexible than the latter ones.